Dissolution Profile of Ibuprofen Solid Dispersion Prepared with Cellulosic Polymers and Sugar by Fusion Method - Saffoon, Nadia; Jhanker, Yeakuty Marzan; Huda, Naz Hasan (Stamford Journal of Pharmaceutical Sciences, 2011)
The purpose of this study was to prepare and characterize solid dispersions of the NSAID Ibuprofen with HPMC, HPC, icing sugar, dextrose, mannitol and lactose with the intention of improving its dissolution properties. The solid dispersions were prepared by the fusion method. Evaluation of the properties of the dispersions was performed using dissolution studies. The results obtained showed that the rate of dissolution of Ibuprofen was considerably improved when formulated in solid dispersions with HPMC and HPC. Solid dispersions with icing sugar, dextrose, mannitol and lactose showed drug retarding capability which may trigger more research in the intension of exploiting this feature to prepare sustained release dosage form. Key words: Ibuprofen; Solid dispersion; Fusion method; Dissolution rate. DOI: http://dx.doi.org/10.3329/sjps.v4i1.8864 SJPS 2011; 4(1): 31-37